Synthesis, Characterization and Comparative Thermal degradation study of Co(II), Ni(ΙΙ) and Cu(II) complexes with Asparagine and Urea as mixed ligands - Mosa’d Jamil, Yasmin; Ali Al-Maqtari, Maher; Mohammed Al-Azab, Fathi; Kassem Al-Qadasy, Mohammed; A. Al-Gaadbi, Amani (Eclética Química, 2018)
New Co(II), Ni(II) and Cu(II) complexes with urea and asparagine as ligands have been synthesized in (M:L1:L2) molar ratio (where M= Co(II), Ni(II) and Cu(II), L1 =urea, and L2 =asparagine) then identified by micro analytical data, molar conductance measurements, IR, 1HNMR, Mass, UV-VIS spectroscopies and magnetic susceptibility measurements. Thermal degradation studies were carried out by thermal analysis. These complexes have the general formula [M(L1)(L2)(H2O)n]Cl. The molar conductance values in DMSO solvent show the electrolytic nature of these complexes, indicating the outer-sphere coordination of the chloride anions with metal ions. The three complexes have an octahedral structure although urea has shown two modes of coordination. Thermal analysis study shows rapid decomposition reaction for Ni complex and the highest thermal stability for Cu complex. The kinetic parameters were determined from the thermal decomposition data using the Coats-Redfern method. Thermodynamic parameters were calculated using standard relations.